THE INFLUENCE OF MECHANICAL AND PHYSICAL AVAILABILITY VALUES ON THE PRODUCTION ACHIEVEMENT RATE OF LOADER AND HAULER UNITS IN OVERBURDEN REMOVAL ACTIVITY OF PT LANGGENG DAYA AGRINDO - Kemas Moh. Ade Isnaeni; Achmad Fauzan Arrahman; Isdaryanto Iskandar (Jurnal Cakrawala Ilmiah, 2022)
One of the factors that can affect the level of production achievement is the availability factor of the mechanical unit used. Theoretically, if the level of availability of a mechanical unit is high, then of course the level of production achievement that can be produced will also be high. However, an statistical analysis was necessary to determine how far this availability factor is in influencing the existing production level. The values of mechanical and physical availability are the example of availability factors which is use generally to evaluate how good is a mechanical unit in conducting its production activities. In this research, the samples were 3 units of loader and 14 units of hauler with the 10 days of data collecting range. From the results of the research conducted, the values of mechanical and physical availability had a strong correlation rate on the production achievement rate of loader unit with the simultaneous influence percentage of 59.49%, but partially it was not significantly influential. The regression similarity of the mechanical and physical availability value influence on the production achievement rate of loader units was Y=-28,6707-1.247,8038 Xâ‚+3.328,7897Xâ‚‚. Then, for the analysis results of the mechanical and physical availability influential values on the production achievement rate of hauler units, it obtained that mechanical and physical availability had a strong correlation rate on the production achievement rate of hauler units with the simultaneous influence percentage of 85.54% and partially, the mechanical and physical availability values were significantly influential on the production achievement rate of hauler units. The regression similarity of the mechanical and physical availability value influence on the production achievement rate of hauler units was Y=113,8621+12.742,1041Xâ‚-9.359,3209Xâ‚‚.